PENERAPAN MODEL PEMBELAJARAN KOOPERATIF METODE QUESTION STUDENT HAVE UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SD NEGERI 187 PEKANBARU - Waslina, Elmita; Alpusari, Mahmud; Syahrilfuddin, Syahrilfuddin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The aims of this research to improve learning result fourth grade science SDN 187 Pekanbaru by implementing cooperative learning methods of question student have. The backgroun of this reserch is the low learning result of science, seen in student value of 37 students. Who are not striking scores of the class was 32 students (86,49%), who reashed the scores of the class was 5 students with an avarage value. The Achievement Standard that school determines 78. The method of research is classroom action research,carried out in two cycles with phases including planning, implementation, observation, and reflection. The technigues of data colection like observation, technique, test and technical documentation. A data colection tod using observation sheet and achievement test. The data analysis technique using teacher and student analysis activity and analysis of student learning result. In cycle I, the first meeting of the teacher gained 62,50% with good category, the second meeting of the percentage increased to 70,83% with good category. In cycle II, the first metting percentage increased to 83,33% in very well category, at the secont meeting the percentage increased to 91,67% with very good category. The average of student learning before the aplication of the model is 55,40 and merease in cycle I to 83,02, and in the second cycle increaset to 87,32, the results showed that the aplication of the cooperative model of question student have method can improve student learning result of science.Key Words: Study Result,Cooperative Learning method question Student have, sciences